Teacher Teaching Strategies and Competencies in Managing Tutoring: A Case Study at Do'a Bunda Bandar Lampung - Wulandari, Martha (Training & Research Institute - Jeramba Ilmu Sukses, 2025)
This study aims to determine and formulate the competencies and teaching strategies used and developed by teachers in managing tutoring institutions. The study was conducted at the Do'a Bunda Tutoring Institution, Bandar Lampung, using a qualitative approach and case study design. Data collection techniques include direct observation of learning activities, in-depth interviews with teachers and institutional managers, and visual documentation, which were then analyzed using thematic techniques. The results of the study indicate that tutoring teachers actively apply and develop four core teacher competencies, namely pedagogical, personality, social, and professional. Pedagogical competence is reflected in the teacher's ability to adjust learning methods and materials to students' learning styles; personality competence is seen in a patient, consistent, and empathetic attitude towards students; social competence is demonstrated through open communication with students and parents, while professional competence is seen in mastery of the material and the use of varied and contextual learning strategies. The teaching strategies used are adaptive, creative, and student-centered, creating a comfortable and productive learning atmosphere. These findings indicate that tutoring teachers can become agents of transformation in non-formal education if they have a deep understanding of their role. The implications of this research not only contribute to improving the quality of learning in tutoring but also emphasize the need for continuous teacher competency training so that the quality of alternative education is increasingly optimal and responsive to students' learning needs.